Global research trends and hotspots on tendon-derived stem cell: a bibliometric visualization study - Zhang, Songou; Shang, Jinxiang; Gu, Zhiqian; Gu, Xiaopeng; Wang, Fei; Hu, Xujun; Wu, Guoliang; Zou, Huan; Ruan, Jian; He, Xinkun; Bao, Chenzhou; Zhang, ZhenYu; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
Purpose: This study was aimed to examine the global research status and current research hotspots in the field of tendon stem cells.Methods: Bibliometric methods were employed to retrieve relevant data from the Web of Science Core Collection (WOSCC) database. Additionally, Citespace, Vosviewer, SCImago, and Graphad Prism were utilized to analyze the publication status in this field, identify the current research hotspots, and present a mini-review.The most active countries in this field were China and the United States.